Distance Constraints: The Limits of Foreign Lending in Poor Economies - MIAN, ATIF (Journal of Finance, 2006)
ABSTRACT How far does mobility of multinational banks solve problems of financial development? Using a panel of 80,000 loans over 7 years, I show that greater cultural and geographical distance between a foreign bank's headquarters and local branches leads it to further avoid lending to “informationally difficult” yet fundamentally sound firms requiring relational contracting. Greater distance also makes them less likely to bilaterally renegotiate, and less successful at recovering defaults. Differences in bank size, legal institutions, risk preferences, or unobserved borrower heterogeneity cannot explain these results. These distance constraints can be large enough to permanently exclude certain sectors of the economy from financing by foreign banks.